The interleukin-7 receptor α chain contributes to altered homeostasis of regulatory T cells in multiple sclerosis - Haas, Jürgen; Korporal-Kuhnke, Mirjam; Schwarz, Alexander; Balint, Bettina; Wildemann, Brigitte (European journal of immunology, 2011)
Treg homeostasis is disturbed in multiple sclerosis (MS). Frequencies of recent thymic emigrant (RTE)-Treg are reduced and the disparity between RTE-Treg and long-lived memory Treg coincides with the MS-associated Treg defect, as shown previously.
First published: 09 December 2010
Gesehen am 25.07.2022